RELATIONSHIP OF EDUCATIONAL INSTITUTIONS WITH THE COMMUNITY - Hifni, Hifni; Susmiyati, Sri; Al Anshori, Habib Anwar (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Educational institutions are an important component in community development. This research aims to explore the relationship between educational institutions and society and their impact on social and cultural development. The methods used are literature studies and surveys with the participation of the community around educational institutions. The research results show that close collaboration between educational institutions and the community can improve the quality of education, strengthen social values, and encourage active community participation in the education process. The conclusions of this research emphasize the importance of synergy between educational institutions and society to create an environment that supports individual and community development